Therapeutic effects of a human antiflagella monoclonal antibody in a neutropenic murine model of Pseudomonas aeruginosa pneumonia. - Oishi, K (1993)
Human immunoglobulin G1 (IgG1) monoclonal antibodies (MAbs) reactive with type-specific Pseudomonas aeruginosa lipopolysaccharide (LPS) and flagella were compared for their protective activities against Fisher immunotype 2 P. aeruginosa pneumonia in neutropenic mice. The activity of the antiflagella MAb at a dose of 500 micrograms per mouse was comparable to that of the anti-LPS MAb at the same dose. In vivo protection was correlated with bacterial density in the lung tissue and blood of infected mice. In vitro data suggested that the protective activity of the antiflagella MAb was due more to inhibition of bacterial motility than to opsonophagocytosis of bacteria by alveolar macrophages. In contrast, the protective activity of the anti-LPS MAb was primarily related to alveolar macrophage-mediated opsonophagocytosis. Antiflagella MAb at a dose of 500 micrograms combined with oral sparfloxacin at a subtherapeutic dose of 62.5 micrograms produced a significant increase in survival (P < 0.05) compared with that produced by either agent alone or no treatment. The additive effects between the antiflagella MAb and sparfloxacin at sub-MICs on the inhibitory effects of bacterial motility supported the in vivo effect of the combination. These data suggest that human isotype-matched antiflagella and anti-LPS MAbs have similar protective activities against Pseudomonas pneumonia in neutropenic mice, despite discrete mechanisms of antibody-matched protection. In addition, in vivo synergy was demonstrated between antiflagella MAb and sparfloxacin in this model.